Application Qualification and Mailing Coordination by Using Sisumaker - Yahya, Ridhony; Irfaniah, Hikmah (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2023)
This study aims to describe the qualification of the Sisumaker as a mailing management application at the Ministry of Law and Human Rights of the Republic of Indonesia and explore how coordination is performed in mailing management within The Sisumaker application. It is qualitative research using the case study method. Therefore, research data were obtained through interviews and observations. Purposive sampling was used to select the informants. Data analysis was done through data reduction, presentation, and conclusion drawing. In this study, the author uses coordination theory as the basis for the research theory. The results show that the Sisumaker application has fulfilled several features needed in a records management application: integrated, web publishing, simple but feature-rich, and portable. Mail management has the same stages as records management: creation and storage, distribution and use, maintenance, and disposition. Coordination of mail management in the Sisumaker application is present at every stage of mail management and involves several components, namely goals, activities, actors, and interdependence. All components complement each other in every stage of records management within the application.